2019
DOI: 10.1186/s12891-019-2405-7
|View full text |Cite
|
Sign up to set email alerts
|

Reference data on hand grip and lower limb strength using the Nintendo Wii balance board: a cross-sectional study of 354 subjects from 20 to 99 years of age

Abstract: BackgroundAccurate assessment of isometric hand grip strength (HGS) and isometric lower limb strength (LS) are often limited to specialized clinics due to high costs and need for specialized equipment and personnel. A mobile and user-friendly device would facilitate a wider use of these measures in the clinical setting. The Nintendo Wii Balance Board (WBB) is a novel and pragmatic tool that has been validated for measuring muscle strength and other clinically relevant physiological variables. However, referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
11
0
2
Order By: Relevance
“…Here, only one study included a measure of lower limb strength in a final model but concluded that this was not superior to simpler questionnaire-based models [ 15 ]. Reasons for this could be because the test does not differentiate well between fallers and non-fallers as the average lower limb strength compares to the background population [ 39 ], and more functional tests of lower limb strength could be more relevant in terms of investigating for predictive performance. This knowledge may be applied when following the current recommendations for falls prevention [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, only one study included a measure of lower limb strength in a final model but concluded that this was not superior to simpler questionnaire-based models [ 15 ]. Reasons for this could be because the test does not differentiate well between fallers and non-fallers as the average lower limb strength compares to the background population [ 39 ], and more functional tests of lower limb strength could be more relevant in terms of investigating for predictive performance. This knowledge may be applied when following the current recommendations for falls prevention [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant level of limbs' strength is fundamental in daily life activities and, moreover, represents a basic quality possessed by physical activity practitioners and athletes in order to maintain physiological body functions and/or enjoy exercise in the best way for the former, and to obtain the best possible results for the latter, respectively [30,31]. In particular, handgrip strength has been considered as marker of health and some studies have demonstrated the correlation between MIHS and global body muscle strength [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In brief, the digit span test was applied to assess the working memory (Martinez-Diaz et al, 2020), where larger values indicate better memory. Maximum hand gripping force is often used to measure age-associated decline in general muscle strength (Eika et al, 2019). The dynamic strength of the legs was assessed by the maximum vertical jump, using linear encoder (Lee et al, 1996).…”
Section: Physiology Testsmentioning
confidence: 99%